Dead time compensation in H-bridge inverters. (2018) - Zammit, Daniel; Apap, Maurice; Staines, Cyril Spiteri
This paper presents the procedure to apply compensation for the distortion created by the dead time/blanking time in H-bridge inverters, as those used in grid-connected photovoltaic (PV) inverters. It also deals with the selection of an appropriate value of dead time, by measuring the turn-on and turn-off times of the switching devices. Dead time/blanking time is needed in H-bridge inverters to prevent 'shoot through' or cross-conduction current through the inverter leg due to the non-ideal nature of the switching devices. The distortion effect of the dead time is analysed by practical experimentation, showing the importance of selecting the most appropriate value of dead time. This is then followed by a procedure to apply compensation to decrease the distortion and thus decrease harmonics caused by the dead time. Both simulation and experimental results will be presented. Testing was carried out on a grid-connected PV inverter which was designed and constructed for this research.